Processes in Kurt Cobain’s Suicide Note - Eva Tuckyta Sari Sujatna; Meita Lukitawati Sujatna (IJFL (International Journal of Forensic Linguistic), 2020)
Many researchers do their research related to Kurt Cobain’s suicide note from Psychology, Public Health or media point of views, but it is limited research related to Forensic Linguistics (FL) and Systemic Functional Linguistics (SFL). The aims of this research are to identify and describe both of processes and verbs expressed in each process in Kurt Cobain’s suicide note. This research is a descriptive study by using qualitative method. It was reported that the four processes involved in the seventy eight clauses as the data that involving various verbs. The four processes found in the data are mental, relational, material, and verbal processes. Firstly, it was found that the mental processes in thirty two clauses with four subtypes process (sixteen clauses of cognitive, nine clauses of emotive, five clauses of perceptive, and two clauses of desiderative). Secondly, it was reported that the relational processes in twenty nine clauses with three subtypes process (twenty one clauses in intensive, seven clauses in possessive, and one clause in circumstantial). Thirdly, it was informed that the material processes in sixteen clauses with two subtypes process (twelve clauses of doing and four clauses of happening). The last, it was discovered that there was only one verbal process in one clause of report.